The World According to Me: Personal Relevance and the Medial Prefrontal Cortex - Abraham, Anna (Frontiers in Human Neuroscience, 2013)
More than a decade of neuroimaging research has established that anterior and posterior cortical midline regions are consistently recruited during self-referential thinking. These regions are engaged under conditions of directed cognition, such as during explicit self-reference tasks, as well as during spontaneous cognition, such as under conditions of rest. One of the many issues that remain to be clarified regarding the relationship between self-referential thinking and cortical midline activity is the functional specificity of these regions with regard to the nature of self-representation and processing. The functional profile associated with the medial prefrontal cortex (mPFC) is the focus of the current article. What is specifically explored is the idea that personal relevance or personal significance is a central factor that impacts how brain activity is modulated within this cortical midline region. The proactive, imaginative and predictive nature of function in the mPFC is examined by evaluating studies of spontaneously-directed cognition, which is triggered by stimulus associated personal relevance.